POLÍTICAS DE CURRÍCULO PARA A DISCIPLINA DE ARTE, NA REDE ESTADUAL DE ENSINO DO PARANÁ: DO FINAL DOS ANOS DE 1980 A 2016 - WEBER, SUZAMARA (2016)
The materiality that underlies this research was based on Brazilian history and its Art, on religious, political, social, cultural and economic influences, manifestations of resistance and the positioning of artists. The goal of this study is to understand the historical trajectory of Art and the curricular proposals of Art discipline in the state public schools network from Paraná, suggested for the final years of elementary education, comprising the period from the end of the 1980‘s to 2016, as its theoretical-methodological foundations considering its socio-historical determinants. For this to take effect, we look at the categories of contradiction and wholeness. The bibliographical research used as a methodological resource, was mainly related to: Marx and Engels (2007), Hauser (1982), Amaral (2003), (2006), Fischer (1987), Vázquez (2010), Nunes (2001), Barbosa (2010), Ferraz and Fusari (2001), Hidalgo; Mello and Sapelli (2010), Sapelli (2003), Cebulski (2007), Stori (2001), Subtil (2012), Bertholdi (2008), Freitas (2007). It was performed a documentary analysis seeking to understand the following proposals: Basic Curriculum for the Public School of Paraná State - CB; National Curricular Parameters of Art - PCN, Curricular Guidelines for Art Basic Education- DCE; And Study Complexes. In order to complement the documentary analysis, was conducted two semi-structured interviews with Basic Education educators who worked in the schools of the state network since the 1990s, and applied two questionnaires to itinerant school educators accompanying the implementation of the related Study Complex proposals to the Movement of Landless Rural Workers - MST. The writing of the dissertation was organized in three chapters. In the first chapter the goal was to turn explicit the materiality of Art in Brazil, for this, was searched for records and data about the Art of the pre-Columbian period to the present day. It was brought elements of the Art prior to the 1500's whose visual, sound and stage expressions had a strong connection with daily life and objective reality and exposed how the colonization presented new demands to the Art in the sense of potentiating European cultural values. It was also present the correlation of forces present in the search for a national identity. It was concluded the chapter with the reflection that Art is also transformed and not isolated from other aspects of society. In the second chapter, after understanding Art as a historical construction, was present how this materiality forged the constitution of the Art discipline in the context of the Brazilian school, including also the processes of regulation and legislation for the teaching of Art. In the third and last chapter, was analyzed the curricular proposals of Art in Paraná state, from the end of the years 1980 to 2016, which presents the historical context, the structure of the documents, as well as the conceptions that these are based. The analysis of the proposals focused on the final years of elementary school. In view of this, was realized that Art in all its manifestations is not isolated, so it is not neutral, and that each curricular movement expresses a demand not only from Art, but also political, social, economic and cultural.